2014
DOI: 10.1159/000357626
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Persistent Storage Symptoms after Transurethral Resection of the Prostate in Patients with Benign Prostatic Enlargement

Abstract: Objective: To identify the prognostic factors causing persistent storage symptoms following transurethral resection of the prostate in patients with benign prostatic enlargement (BPE). Methods: A total of 116 men with symptomatic BPE requiring surgery were enrolled in the study between January 2011 and December 2012. The patients underwent basic clinical evaluations including transrectal ultrasound, International Prostate Symptom Score and urodynamic study. After 6 months, International Prostate Symptom Score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 23 publications
4
44
1
Order By: Relevance
“…In contrast to a previous study , we found no correlation between patient age and reduction in symptoms after PAE. While in the TURP group in the trial, younger patients (<70 vs ≥70 years) had a more distinct improvement in IPSS, which is in line with previous studies on transurethral surgical techniques , this correlation was not found after PAE.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to a previous study , we found no correlation between patient age and reduction in symptoms after PAE. While in the TURP group in the trial, younger patients (<70 vs ≥70 years) had a more distinct improvement in IPSS, which is in line with previous studies on transurethral surgical techniques , this correlation was not found after PAE.…”
Section: Discussionsupporting
confidence: 89%
“…In a retrospective study by Zhao et al involving 128 BPH patients, the outcomes of patients with mild preoperative SS were shown to be much better than those with moderate and severe symptoms (7). In Choi et al 's study with 116 patients, multivariate analysis has shown that poor initial SS were a risk factor for persistent SS in the postoperative period (OR=8.32) (10). In a study by Porru et al including 60 patients, postoperative symptom scores were shown to get worse in patients with significant preoperative SS (p=0.001) (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is important for the surgeon and patients to know which group of patients is under risk for development of OABS after TURP. Several studies have shown that the success rates in the postoperative period were lower in patients with preoperative urodynamic detrusor overactivity (DO) and preoperative severe SS, although the data on this subject are contradictory (4)(5)(6)(7)(8)(9)(10)(11). So there is no consensus in this issue, which therefore needs further studies.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects everyday reality of referral, but is a concern since outcomes of surgery to treat BOO are less reliable where storage LUTS are problematic [25]. In particular, nocturia was highly prevalent and bothersome (IPSS, ICIQ-MLUTS and bladder diary), yet nocturia often reflects systemic conditions unrelated to LUTS [9].…”
Section: Discussionmentioning
confidence: 99%